Respuestas

¡La mejor respuesta!
2013-09-19T18:47:25+02:00
A) 2^1/3.2^1/5 = 2^(1/3+1/5) = 2^8/15 = raiz 15 de 2^8
b) (3^2)^1/3.3^1/6 = 3^2/3.3^1/6^ = 3^(2/3+1/6) = 3^5/6 = raiz 6 de 3^5
c) 2^1/2.2^1/4.2^1/8 = 2^(1/2+1/4+1/8) = 2^7/8 = raiz 8 de 2^7
d) (2^3)^1/4.(2^2)^1/3 = 2^3/4.2^2/3 = 2^(3/4+2/3) = 2^17/12 = raiz 12 de 2^17

a) x^(1/5 - 1/3) = x^-2/15 = (1/x^2)^15 = (1/x)^15 = x^-15
b) (a - b)^(1/2 - 1/3) = (a - b)^1/6 = raiz de (a - b)
muchas gracias! me diste una mano!
Suerte!
hay alguna forma de agregarte a Amigos o algo por el estilo?